2022
DOI: 10.3390/ijerph19138056
|View full text |Cite
|
Sign up to set email alerts
|

Novel Options to Counteract Oral Biofilm Formation: In Vitro Evidence

Abstract: Biofilm production on biotic and abiotic surfaces is crucial in the pathogenesis of most infections, particularly those occurring in the oral cavity. Its prevention and/or control may greatly facilitate the management of patients with oral diseases. Here, the antibiofilm activity of a biomimetic hydroxyapatite and a natural compound, MicroRepair (MicroR) and pomegranate (PomeGr), respectively, was assessed. By luminescence/fluorescence-based assays, Pseudomonas aeruginosa (P. aeruginosa), Staphylococcus aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Kupnik et al described the antimicrobial activity of plant extracts, including Punica granatum L. [ 34 ]. Recently, we have provided initial evidence on the ability of PomeGr to affect biofilm formation by both fungal and bacterial cells [ 25 ]. To better understand the phenomenon, here, we demonstrate that PomeGr exerts anti- Candida activity in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kupnik et al described the antimicrobial activity of plant extracts, including Punica granatum L. [ 34 ]. Recently, we have provided initial evidence on the ability of PomeGr to affect biofilm formation by both fungal and bacterial cells [ 25 ]. To better understand the phenomenon, here, we demonstrate that PomeGr exerts anti- Candida activity in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 , 24 ]. Recently, we provided initial evidence on the efficacy of PomeGr against biofilm production by C. albicans and Pseudomonas aeruginosa as well [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dental caries management philosophy has shifted to minimally invasive dentistry [ 35 , 36 ]. Thus, different bioactive materials, such as biomimetic hydroxyapatite and peptide-based bioactive materials, are introduced to caries management [ 37 , 38 ]. Peptide-based bioactive materials play an important role in inhibiting biofilm growth and remineralising demineralised teeth [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the dental field, hydroxyapatite is often focused on enamel remineralization rather than its effect on oral bacteria. However, recent in vitro studies have shown that toothpaste containing hydroxyapatite reduces saliva's oral bacterial counts and biofilm levels [13,14].…”
Section: Introductionmentioning
confidence: 99%